Challenges and responses: A Complex Dynamic Systems approach to exploring language teacher agency in a blended classroom - Qi GY; Wang Y (Castledown Publishers)
This is a qualitative examination of how a Chinese language teacher responded to challenges and developed her agency in a unique teaching and learning environment, termed as the blended classroom. The uniqueness of this classroom lies in its attendance by two cohorts of students at the same time – the face-to-face and the online groups. The online group joined the face-to-face group and the teacher via a synchronous online classroom called Blackboard Collaborate. Through analysing data from the teacher’s reflection, face-to-face and email interviews and the recordings of her blended class, this research unfolds a semester-long trajectory of her agency development in the blended classroom. Guided by the Complex Dynamic Systems Theory (CDST), we conclude that teacher agency is a system composed of multi-layers of subsystems and it is a product of the constant interaction amongst these interconnected and interdependent subsystems, with certain subsystems playing a more dominant role than others at a given stage of one’s agency development. This finding led to our proposal of a framework of teacher agency system. This research advances our understanding of teacher agency as a system in the context of online and blended learning.
Keywords: Complex Dynamic Systems Theory (CDST); teacher agency; language teaching; blended learning; blended classroom; 1302 Curriculum and Pedagogy; 1702 Cognitive Sciences; 2003 Language Studies